(untitled) (Olhar de Professor, 2022)
In view of technological advances, which make knowledge to be disseminated in different ways and through increasingly sophisticated resources, this paper proposes the analysis of the superhero Ant-Man’s movies, from the perspective of Physics Teaching, for themes of Modern and Contemporary Physics. Our analysis aimed to select scenes from the film that can be used to explain complex and abstract concepts, such as those related to Quantum Physics, in addition to analyzing the veracity of physical phenomena present in the films. To support the relevance of these discussions, a survey was made of the works published in the two largest events related to Physics Teaching in Brazil: the EPEF and the SNEF, where we found a considerable number of works produced in this sense. From this research, we can see the effectiveness of using these films in the classroom, making the teaching-learning process more meaningful.